Pengaruh Mekanisme Corporate Governance dan Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Kesehatan yang Terdaftar di BEI Tahun 2022-2024 - Nazwa Salsa Safira Mayani; Nova Ajika Firmansyah; Nabila Putri Andriawan; Laili Dhurrotun Nafisa; Aulia Putri Dewi Kartika Sari; Tiara Dwi Rizqianti; Rohmawati Kusumaningtias; Ambar Kusumaningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study aims to analyze the effect of corporate governance mechanisms (managerial ownership, institutional ownership, independent commissioners, and audit committee) and financial performance (Return on Assets and Return on Equity) on firm value in healthcare sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2022–2024. The population consists of all healthcare sector manufacturing companies listed on the IDX, with a sample of 84 observations selected using purposive sampling. The analytical method used is multiple linear regression with SPSS. The results of classical assumption tests indicate that the data are normally distributed, with no multicollinearity or heteroscedasticity, but positive autocorrelation is present. The regression results show that partially, only institutional ownership has a positive and significant effect on firm value at ? = 0.05, while managerial ownership, independent commissioners, ROA, and ROE have no significant effect. The Adjusted R Square value of 0.037 indicates that only 3.7% of the variation in firm value is explained by the six independent variables, while the remaining 96.3% is explained by other variables outside the model. In conclusion, institutional ownership plays an important role in increasing firm value, but the overall model has limitations due to autocorrelation and low explanatory power. Future research should expand the sample, extend the observation period, and include additional variables such as firm size, leverage, and dividend policy. This study contributes to the literature on corporate governance and firm value in the healthcare sector during the post-pandemic recovery period.